Critiquing the logic of the domain section of the occupational therapy practice framework: domain process. - Nelson DL (American Journal of Occupational Therapy)
The Occupational Therapy Practice Framework: Domain and Process (also known as the Framework), an official document of the American Occupational Therapy Association, advocates terminology and a classification system for concepts that are central to the profession of occupational therapy. Its use has been advocated in practice, research, education, and communications with those who wish to know more about occupational therapy. Given its importance to the profession and to society, the Framework deserves intense scrutiny and sustained scholarly inquiry. This article investigates the logic of Occupational Therapy Practice Framework: Domain and Process, with a focus on domain. Are definitions and classifications within the domain logically coherent? The Framework repeatedly violates two rules of logical definitions: (a) a unique term must be applicable to certain particulars and must not be applicable to others (the rule of precision); and (b) the particulars assigned to one term must not be assignable to another term unless there is a logical explanation (the rule of parsimony). The Framework also repeatedly violates two rules of logical classification: (a) a lower-level category must be classifiable only within its assigned higher-level category (the rule of exclusivity); and (b) all relevant particulars must be classifiable (the rule of exhaustiveness). The profession of occupational therapy needs one or more logically coherent conceptual frameworks, but the Framework is not recommended as a logical basis for practice, education, research, and external communications. Specific recommendations are made in support of the development of a logical framework and the refinement of existing frameworks.